Разбой в открытом море: роман / С. И. Зверев - Зверев С. И. (Морской спецназ, 2012)
Экземпляры: (20190305) / Инвентарный номер: 31401 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-43 / ББК: 84(2Рос=Рус)6